Strategi Pengelolaan Persediaan UMKM (MCREPES di Surabaya) Agar Tetap Kompetitif di Pasar - Lea Berliana Jeni Salih; Sri Rahayuningsih (Universitas 45 Surabaya, 2025)
One of the key components of success for small and medium enterprises (SMEs), including crepes businesses, is inventory management. This article discusses effective inventory management strategies to enhance operational efficiency and competitiveness of crepes SMEs in the market. Some of the methods discussed include the Just in Time (JIT) method to minimize raw material waste, demand forecasting based on sales data, and leveraging digital technology such as inventory applications to monitor stock in real time. Another strategy highlighted is the ABC classification method to categorize raw materials based on value and priority levels, establishing safety stock to anticipate uncertainties, and fostering collaboration with suppliers to ensure the availability of high-quality raw materials. By implementing these strategies, crepes SMEs are expected to manage their inventory more efficiently, reduce the risk of stock shortages or overstocking, and remain competitive in an increasingly challenging market.